Physicochemical Properties and Antioxidant Activity of Chicken Sausage with Addition of Roselle Extract (Hibiscus sabdariffa) and Different Filler Ratio - Jamhari Jamhari; Aryanti Candra Dewi; Setiyono Setiyono (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study was done to determine the effect of Roselle extract level (Hibiscus sabdariffa), and the wheat flour and mocaf flour ratio, as well as the interaction between the Roselle extract level and the wheat flour and mocaf flour ratio on the chemical, physical, and antioxidant activity of chicken sausage. The ingredients used were chicken meat, wheat flour, mocaf flour, Roselle extract, skim milk powder, and spices. Roselle extract levels were 0, 4, and 8% (v/w of total dough) and ratio of wheat flour : mocaf flours were 100:0, 50:50 and 0:100. Parameters observed included chemical composition (moisture, protein, and fat contents), physical properties (pH value and tenderness), and antioxidant activity of chicken sausage. Data were analyzed by analysis of variance of 3x3 factorial and continued by Duncan's new multiple range test test. The results of statistical analysis showed that Roselle extract level gave a significant effect (P<0.05) on moisture content, pH value, and antioxidant activity of chicken sausage. Ratio of wheat flour : mocaf flour gave a significant effect (P<0.05) on protein content, tenderness and antioxidant activity of chicken sausage. There was no interaction between Roselle extract level and the wheat flour : mocaf flour ratio on the physicochemical properties and antioxidant activity of chicken sausage. The conclusion of this study is the addition of Roselle extract upto 8% will increase moisture content and antioxidant activity, but it decreases the pH value and tenderness of chicken sausage. Subtitution of wheat flour with mocaf flour will reduce protein content, tenderness and antioxidant activity of chicken sausage.